2015
DOI: 10.1007/s10164-015-0425-9
|View full text |Cite
|
Sign up to set email alerts
|

White-rumped swallows prospect while they are actively nesting

Abstract: Nest prospecting, that is, visiting potential future nest sites, may be a widespread bird behavior. Here we describe apparent prospecting while nesting by whiterumped swallows (Hirundinidae, Aves). In southern Brazil, birds tagged with passive-integrated transponders (PITtags) and breeding in nest boxes with PIT-tag readers: (1) often visited nest boxes that were in use by apparently unrelated birds (54 % of nests were visited at least once), (2) visited other boxes while caring for their own nestlings, (3) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Tree swallows are one of the best-studied species of birds outside of the laboratory. Although visits to other boxes have been documented previously (Lombardo 1986(Lombardo , 1987bWischhoff et al 2015), the extent of social visitation to other boxes that we uncovered was surprising and was made possible only because of the novel use of RFID technology at each active nest-box. This technology has been used to quantify social interaction networks at central food resources (Adelman et al 2015;Psorakis et al 2015;Ellwood et al 2017), but has not been used nearly as extensively in quantifying social interactions at nest locations, which may have quite different functions than social associations within a foraging flock.…”
Section: Discussionmentioning
confidence: 84%
“…Tree swallows are one of the best-studied species of birds outside of the laboratory. Although visits to other boxes have been documented previously (Lombardo 1986(Lombardo , 1987bWischhoff et al 2015), the extent of social visitation to other boxes that we uncovered was surprising and was made possible only because of the novel use of RFID technology at each active nest-box. This technology has been used to quantify social interaction networks at central food resources (Adelman et al 2015;Psorakis et al 2015;Ellwood et al 2017), but has not been used nearly as extensively in quantifying social interactions at nest locations, which may have quite different functions than social associations within a foraging flock.…”
Section: Discussionmentioning
confidence: 84%
“…The study area in southern Brazil (25.50°S, 49.05°W) consists of two colonies, ca. 5 km apart, with regularly mowed lawns, sparse groups of trees, and marshes (Wischhoff et al., ). During this study, 139–149 wooden nest‐boxes of similar design (17 × 13 × 25 cm) were available to breeding birds.…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative, swallows exhibit another behavior to explore the environment. This behavior is the prospection of cavities and supposedly allows them to occupy better nest‐sites in the future (Lombardo, ; Wischhoff, Marques‐Santos, Ardia, & Roper, ). Prospecting behavior may be a personality trait in swallows because it was found to be consistent in jackdaws ( Corvus monedula ; Schuett, Laaksonen, & Laaksonen, ).…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of the breeding season, breeders separate from the flock to start their reproductive activities (Archawaranon, 2003). A difficult challenge and an ecological constraint of Hill Mynahs is that they are secondary nest-cavity breeders, with heavy competition for nest sites (Bonebrake and Beissinger, 2010); this can limit their reproductive success (Karlsson, 1983;Wischhoff et al, 2015). Studies of Hill Mynah breeding in the wild have shown that male and female Hill Mynah aggressively chase away other couples from encroaching a tree in which they have already established their nests, and there are never two or more breeding pairs nested in the same tree even if the tree has a number of cavities (Archawaranon, 2003(Archawaranon, , 2006.…”
Section: Discussionmentioning
confidence: 99%